PELATIHAN PEMBUATAN KONEKTOR MASKER MENGGUNAKAN BAHAN LIMBAH KONVEKSI PADA KARANG TARUNA DESA MEKARMUKTI - Riky Oktaviana; Rukanda, Nandang; Ansori, Ansori (Jurnal Empowerment, 2025)
The training aim to increasing and strengthening the potential of Mekarmukti Village residents towards a healthy, intelligent and empowered society by utilizing materials from convection waste to make mask connectors, where masks are a primary or mandatory need for everyone during a pandemic like now. This activity begins with observations and interviews after that, its implementation using method training and mentoring for youth organizations in Mekarmukti village, numbering 10 people. The results of this activity show a positive impact in increasing the skills and awareness of members of the Mekarmukti Village youth organization in managing convection waste.